2003
DOI: 10.1002/jsfa.1371
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative effects in uninfected tissue in leaves of French bean (Phaseolus vulgaris) containing soft rots caused by Botrytis cinerea

Abstract: Several markers of oxidative processes have been measured in leaves of Phaseolus vulgaris infected with Botrytis cinerea, with the specific objective of investigating changes induced by this necrotrophic pathogen in tissue remote from the lesion. There was a progressive decrease with time in the contents of ascorbic acid (AA) in apparently healthy tissues from infected plants and non-inoculated plants grown under identical high-humidity conditions (abiotically stressed controls), and for periods >48 h this dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…This is perhaps not surprising because of the large numbers of molecules in biological systems that are capable of participating in free radical reactions. Many scientists have reported the formation of the ascorbate radical (with a characteristic doublet spectrum having g = 2.0053, a ( 1 H) = 0.18 mT) in physically damaged and abiotically stressed tissue (see eg Refs 31 and 33). This signal could not be identified in the present work, because the broader linewidths of rigid‐limit spectra render the 1 H hyperfine structure unobservable.…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps not surprising because of the large numbers of molecules in biological systems that are capable of participating in free radical reactions. Many scientists have reported the formation of the ascorbate radical (with a characteristic doublet spectrum having g = 2.0053, a ( 1 H) = 0.18 mT) in physically damaged and abiotically stressed tissue (see eg Refs 31 and 33). This signal could not be identified in the present work, because the broader linewidths of rigid‐limit spectra render the 1 H hyperfine structure unobservable.…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical staining in Botrytis ‐infected Arabidopsis leaves revealed that the oxidative burst in a compatible interaction comprises the simultaneous production of hydrogen peroxide and nitric oxide, as well as the formation of proteolytic, autophagosome‐like vesicles at the host–pathogen interface (van Baarlen et al ., 2007). B. cinerea infection leads to the accumulation of free radicals, both at the host–pathogen interface and at some distance from the invading hyphae (Muckenschnabel et al ., 2001a, 2003) culminating in lipid peroxidation (Deighton et al ., 1999; Muckenschnabel et al ., 2001b, 2002) and depletion of antioxidants (Muckenschnabel et al ., 2002). Altogether, these oxidative processes cause massive perturbation of the redox status in and around the infected tissue, thereby promoting disease progress (Lyon et al ., 2004).…”
Section: Infection Requires Active Participation By the Hostmentioning
confidence: 99%
“…It has recently been shown that B. cinerea produces ROS in axenic culture and in planta : cytochemical analysis showed the presence of in hyphal tips and H 2 O 2 generation in and around the penetrated cell wall (Tenberge et al ., 2002). There is other clear evidence for ROS and the involvement of other markers of oxidative stress in tissues attacked by B. cinerea (Deighton et al ., 1999; Muckenschnabel et al ., 2001a,b, 2002, 2003).…”
Section: Introductionmentioning
confidence: 99%